Analysis of The Performance and Financial Capabilities of The Mataram City Government for The 2019-2023 Fiscal Year - Nurfadila Aulia Sanna; Akhmad Jufri; Eka Agustiani (International Journal of Economics Studies, 2026)
The purpose of this study is to determine the performance and financial capabilities of the Mataram City Government for the 2019-2023 fiscal year. This type of research is quantitative descriptive. The data used are primary data and secondary data. The results of the study are:1). The level of financial independence shows that the Mataram city government already has a fairly good independence with a criterion of 51%. 2). The level of financial effectiveness of the Mataram city government in collecting PAD tends to be very effective with a percentage of 100%. The level of financial efficiency of the local government of Mataram city is inefficient in using the budget optimally with a percentage of 111%. 3). The level of financial activity of the Mataram city government still prioritizes regional spending for direct spending rather than indirect spending, 4). The growth rate of PAD and TPD of the Mataram city government shows that the average growth of PAD is 7% and TPD is 3%. The Mataram City Government prioritizes direct spending, with an average of 2%, compared to indirect spending which is only 1% on average. 5). The degree of fiscal financial decentralization of the Mataram City Government has regional fiscal independence that is quite optimal with a percentage of 37%. Overall, the financial performance of the Mataram City Government shows progress in the effectiveness of PAD collection and a fairly good level of financial independence, although the region is still dependent on central fund transfers.